Australia's north, Australia's future: A vision and strategies for sustainable economic, ecological and social prosperity in northern Australia. Issue 3 (22nd September 2018) - Chambers, Ian; Russell‐Smith, Jeremy; Costanza, Robert; Cribb, Julian; Kerins, Sean; George, Melissa; James, Glenn; Pedersen, Howard; Lane, Paul; Christopherson, Peter; Ansell, Jennifer; Sangha, Kamaljit
Abstract: The release of the United Nations Sustainable Development Goals and the Paris Climate Change agreement highlighted the importance of global sustainability internationally. Here, we outline a vision and strategies for developing northern Australia that demonstrate how a focus on sustainable prosperity can both expand historical approaches and current government plans and integrate the biophysical realities with the social, political, and cultural characteristics of the region. We highlight examples of the significant horizontal and vertical integration opportunities that this expanded vision and related strategies provide for (a) land (carbon farming, targeted food production systems, and native title arrangements); (b) water (water resources management); (c) energy (renewable energy production, storage, and distribution); (d) workforce (culturally appropriate ecotourism, Indigenous ranger programs, and protected area management); (e) knowledge services (health care and innovative employment opportunities); and (f) governance (greater participatory governance). We found that realisation of even 10% of these emerging opportunities over the next 10 years alone could result in economic growth worth over AUD 15 billion and 15, 000+ jobs for northern Australia as well as the further ecological and social benefits derived from a sustainable prosperity strategy.